Wydział Teologii Katolickiego Uniwersytetu Lubelskiego Jana Pawła II - Lizut, Marta (Studia Nauk Teologicznych PAN, 2020)
Th e Th eology Department was opened in January 1918. It came into existence as one of the fi rst four departments of the Catholic University of Lublin. Its activity became part of the university’s mission which is conducting research in harmony with science and faith, educating the catholic intelligentsia and contributing to christian culture. Th e identity of the Department manifests itself in the high standard of scientific research and academic education as well as in deepening and promoting the christian concept of the world and man in the context of challenges of the present time.This article presents an outline history, organization and the main trends in scientifi c research carried out in the Th eology Department of John Paul II Catholic University of Lublin.